1986
DOI: 10.1002/qsar.19860050405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Binding Energetics in Paper and Thin‐Layer Chromatography

Abstract: The binding of organic compounds to inorganic and organic polymers can be resolved by multiple regression analysis of adsorption data. Such data are provided indirectly by adsorption chromatography retentions or directly through measured heats of adsorption. This study uses chromatographic data to explore the nature of low energy binding events in terms of a primary binding descriptor (log P or MR) modified by electronic, steric, and sub‐structural descriptors. Mechanistic details are clearly revealed in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Binding energy then, is revealed as an additive-constitutive process which should yield to detailed analysis by a factoring procedure. In recent studies of the binding of small molecules to organic and inorganic polymers, we have found that binding is not a molecular process but rather one involving, at most, a few key positions [14]. We are encouraged by this and by Andrew's work to hope that binding to active sites may involve only a fraction of the whole molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding energy then, is revealed as an additive-constitutive process which should yield to detailed analysis by a factoring procedure. In recent studies of the binding of small molecules to organic and inorganic polymers, we have found that binding is not a molecular process but rather one involving, at most, a few key positions [14]. We are encouraged by this and by Andrew's work to hope that binding to active sites may involve only a fraction of the whole molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of large sets, it is possible to define different regions of lipophilicity (rdependant) and polarizability (MR-dependant) as in a recent study of DHFR binding [6], as well as mixed behaviour in the same region [14]. Thus.…”
Section: Introductionmentioning
confidence: 99%